THE USE OF DEMONSTRATION TECHNIQUE IN IMPROVING LEARNERS’ SPEAKING ABILITY - Ade Muhamad Ismail Marzuqi; Debi Firdaus (IKIP Siliwangi, 2019)
This study aims to develop learners’ speaking skill at tenth grade of SMK Budi Bakti Utama through Demonstration Technique in procedure text. This research is a Classroom Action Research based on Kurt Lewin’ design. This CAR done in two cycle. Every cycle consist of four phases (planning, acting, observing and reflecting). The data were gathered through qualitative and quantitative, namely interview, observation, pretest, posttest and questionnaire. The researcher found that demonstration Technique in teaching procedural text was succes to increase the learners’ speaking ability. It is concluded from the learners score. Where, before implementing CAR the mean score was 53.48 and only 6 learners from 33 learners passed the KKM. Then, after implementing CAR the mean score was better became 75.21 and there are 27 learners passed the KKM.